A heterogeneous perspective of brand community - Roy, Rajat; Phau, Ian; Lee, Thomas (Society for Global Business and Economic Development, 2011)
Current view on brand community conceptualizes the construct as a collection of highly homogeneous members despite some recent evidence that community members might be heterogeneous. Extant scholars call for more research to establish sources of such heterogeneity. This article shows that members of a brand community e.g. fans of a sports club, can be meaningfully segmented into clusters based on relationships that consumers may have with a brand community e.g. with the product, brand, organization, and other consumers. Using data from a large survey, we apply cluster analysis techniques to meaningfully segment the fans of a sports club. Further, based on arguments from sports marketing literature, we establish that these clusters can vary significantly in terms of their psychological underpinnings like different motivations to consume sports.